Research on the damage evolution law of iron tailing sand based foam concrete under cyclic loading - Xiaoli Du; Liping Zhu; Yanyan Li; Haowei Wang; Kai Xu (Case Studies in Construction Materials)
In order to investigate the dynamic response of iron tailing sand based foam concrete as a roadbed filler, graded cyclic loading and unloading tests were carried out in this paper to examine its dynamic properties. The hysteresis curve, fatigue strength, loading-residual strain, energy evolution and microstructure were investigated and analyzed, taking into account the influencing factors of different iron tailing sand contents. The results show that the hysteresis curve exhibits obvious elastic-plastic characteristics, the main curve has an approximate hyperbolic shape, and the cyclic loading and unloading strengths are lower than the uniaxial compressive strength. The sensitivity of the residual strain to the stress change is lower than the loading strain. With the increase of iron tailing sand content, the number of cyclic loading-unloading experienced by the pieces showed a trend of increasing and then decreasing, and the energy dissipation capacity was improved to a certain extent.